دور وزارة الأوقاف والشؤون الإسلامية بدولة قطر في تنظيم المسابقات القرآنية وسبل تقويمها: The role of the Ministry of Endowments and Islamic Affairs in organizing Quranic competitions in Qatar and ways to evaluate them - Alqahtani, Sulaiman Jamaan; Nashwan Abdo Khaled, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث إن حب التسابق والتنافس أمرٌ جُبلت عليه النفوس البشرية، ولذلك فإن فكرة المسابقات وجدت منذ عصور قديمة، ولكل عصر وجيل مسابقات مختلفة، ومن هذه المسابقات ما يُقام في عصرنا من المنافسة والتسابق في القرآن الكريم وعلومه، وتكمن مشكلة البحث في ضعف توثيق هذه المسابقات القرآنية التي مرّت في أطوار مختلفة دون توثيق وتطوير، ولذا فإن هذا البحث يهدف إلى توثيق المسابقات القرآنية المنظمة من قبل وزارة الأوقاف والشؤون الإسلامية بدولة قطر مع طرح حلول تقويمية تساهم في تطوير تلك المسابقات، وقد استخدم البحث المنهجين الاستقرائي والتحليلي لعرض الموضوع وتحليل مفرداته وأقسامه، وخلص البحث إلى مجموعة من النتائج من أبرزها: اهتمام وزارة الأوقاف والشؤون الإسلامية بدولة قطر بالمسابقات القرآنية مادياً وفنياً وتقنياً. ABSTRACT The love of competition and rivalry is a natural inclination of the human soul. For this reason, the concept of competitions has existed since ancient times, with each era and generation having its own unique competitions. Among these competitions are those held in our time, focusing on the Quran and its sciences. The problem this research addresses is the lack of documentation for these Quranic competitions, which have undergone various phases without adequate recording or development. Therefore, this research aims to document the organized Quranic competitions conducted by the Ministry of Awqaf and Islamic Affairs in the State of Qatar, while also proposing evaluative solutions to enhance these competitions. The research employed both inductive and analytical methods to present the topic and analyze its components and sections. The study concluded with several Fīndings, the most notable being the Ministry of Awqaf and Islamic Affairs in Qatar's signiFīcant interest in Quranic competitions in terms of Fīnancial, technical, and artistic support.